2014
DOI: 10.3389/fpsyg.2014.00192
|View full text |Cite
|
Sign up to set email alerts
|

Approach-avoidance activation without anterior asymmetry

Abstract: Occasionally, the expected effects of approach-avoidance motivation on anterior EEG alpha asymmetry fail to emerge, particularly in studies using affective picture stimuli. These null findings have been explained by insufficient motivational intensity of, and/or overshadowing interindividual variability within the responses to emotional pictures. These explanations were systematically tested using data from 70 students watching 5 types of affective pictures ranging from very pleasant to unpleasant. The stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…We also observed the distribution density of the two dimensions on the whole training dataset, shown in Figure 8. The density observed in Figure 8 showcases a similar distribution as in [20], [44] and [1]. There is a whole research branch on learning data distributions.…”
Section: Outlier Regularisation On Predicted Labelssupporting
confidence: 67%
See 1 more Smart Citation
“…We also observed the distribution density of the two dimensions on the whole training dataset, shown in Figure 8. The density observed in Figure 8 showcases a similar distribution as in [20], [44] and [1]. There is a whole research branch on learning data distributions.…”
Section: Outlier Regularisation On Predicted Labelssupporting
confidence: 67%
“…This may be caused by the noise in the handcrafted emotion annotations. In [20], [44] and [1], the labelled data presents a similar oval shape, instead Session: Gold-standard Emotion Sub-challenge AVEC'18, October 22, 2018, Seoul, Republic of Korea of a strict bipolar distribution or a U shape. Also, the research so far was on discrete emotion labels instead of continuous annotations.…”
Section: Distribution Of Valence and Arousalmentioning
confidence: 99%
“…The findings of this review revealed that picture presentation could induce approach-avoidance effects if the images were particularly emotionally relevant for the sample group, for instance anxiety-relevant pictures shown to patients with panic disorder (Wiedemann et al, 1999). Thus, for a general sample group, affective images alone might be insufficient to create motivational engagement while stimulus-relevant personal characteristics can potentiate frontal alpha asymmetry (Harmon-Jones et al, 2006;Gable and Harmon-Jones, 2008;Uusberg et al, 2014;Rejer and Jankowski, 2017). Consistent with this, significant correlations have been found between frontal alpha asymmetry and differences in emotive tendencies (e.g., dessert liking) or personality traits (Wacker et al, 2008; for examples see Gable and Harmon-Jones, 2008;Uusberg et al, 2015;Winter et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Secondly, we baseline-normalized the EEG signal acquired during the presentation of the commercial scripts by using the Decibel conversion formula. As a matter of fact, some studies highlighted that possible interindividual trait predispositions of FAA, measured during a baseline EEG registration, may shape the variability of the FAA collected during an experimental task (i.e., Uusberg et al, 2014).…”
Section: Discussionmentioning
confidence: 99%